Thermogravimetric analysis (TGA) results of bulk organic matter in permafrost from the Lena Delta, Arctic - Lin, Tsai-Wen; Nehrke, Gernot; Mollenhauer, Gesine (In: Lin, T-W et al. (2025): Bulk organic matter data of Lena Delta permafrost, marine surface sediment, and sediment cores from the Laptev Sea, Arctic Ocean [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984732, 2025)
This datasheet includes the results of thermogravimetric analysis (TGA) from permafrost samples collected from the Lena Delta. Sediment samples of ~20 mg were dried, ground, and analyzed in 70 μL aluminum oxide crucibles using a Mettler Toledo TGA/DSC 1. The samples were heated from 25 to 1000 °C at a rate of 10 °C min-1 under a constant argon flow of 20 mL min-1, following similar settings from Smeaton & Austin (2022). Following Lopez-Capel et al. (2006), weight loss between 200–400 °C is attributed to the decomposition of labile organic matter (OML), while weight loss between 400–650°C corresponds to the decomposition of recalcitrant and refractory organic matter (OMR). The percentage of labile organic matter (OML/OM) is calculated as [OML/(OML+OMR)]*100%
Keywords: Arctic; labile OM; Lena Delta; OML; OMR; permafrost; refractory and recalcitrant OM; TGA; thermogravimetric analysis